5-{[(E)-2-(4-Iodophenyl)hydrazinylidene]methyl}thiophene-2-carbaldeh yde - Wardell, S.M.S.V.; de Lima, G.M.; Tiekink, E.R.T.; Wardell, J.L. (International Union of Crystallography, 2010)
The title compound, C(12)H(9)IN(2)OS, has an overall U-shape, with a dihedral angle of 21.4 (3)degrees between the thiophene and benzene rings. In the crystal, supramolecular chains mediated by N-H center dot center dot center dot O hydrogen bonds are formed along the b-axis direction.